PHILOSOPHICAL AND PSYCHOLOGICAL ASPECTS OF MUSIC PERCEPTION AND MEMORY STUDY - Anna A. Rybak (Advanced Engineering Research, 2012)
Some certain theoretical and experimental studies on the historical origin of music, musical perception, and musical memory are analyzed. Various directions for this problem research are classified.